Pengentasan Kemiskinan Melalui Pembangunan Sistem Transportasi Perdesaan - Harun, Uton Rustan (Center for Research and Community Services ITB, 1999)
The rural road is expected to alleviate the rural poverty in IDT (presidential Decree for Undeveloped Village) programme. Although this programme is still running during the economic crisis (namely Social Safety Net Programme) there are some questions of the effectiveness of the programme. Rural road development and rural transportation system should be designed well to meet this objective. What is necessary is an understanding of the interaction of rural roads, transportation modes and socio-economic factor of rural development. Even the uses of participatory planning programe in deciding the rural roads programme, may not solve the problem of targeting benefit to the poorest segments of rural society.